2009
DOI: 10.1002/ejsp.617
|View full text |Cite
|
Sign up to set email alerts
|

Prejudice in the police: On the processes underlying the effects of selection and group socialisation

Abstract: The principal aim of this study is to determine why police officers are generally found to be more prejudiced towards disadvantaged groups than are the standard population. Two independent processes were expected to account for this effect: Selection and group socialisation. Using a cross-sectional design (N ¼ 170), firstly, we compared, newly recruited police officers with a control population (selection effect), and secondly, police officers with 1 year of training with the newly recruited ones (group social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 51 publications
1
39
0
6
Order By: Relevance
“…Just so, the two studies focusing on the direct comparisons of occupational groups and the three studies that compare people of different religious orientations are not able to determine whether group membership is responsible for animal attitudes (socialization effect) or whether people join groups based on their preexisting attitudes toward animals (selection effect). Longitudinal studies are needed to disentangle the role of these socialization and selec tion effects, and test how they operate over time (e.g., Gatto, Dambrun, Kerbrat, & De Oliveira, 2010). Experiments that employ situational manipulations of norms relating to humananimal relations (Smith & Louis, 2008) could also be employed in future research.…”
Section: Methodological Implications and Future Research Directionsmentioning
confidence: 99%
“…Just so, the two studies focusing on the direct comparisons of occupational groups and the three studies that compare people of different religious orientations are not able to determine whether group membership is responsible for animal attitudes (socialization effect) or whether people join groups based on their preexisting attitudes toward animals (selection effect). Longitudinal studies are needed to disentangle the role of these socialization and selec tion effects, and test how they operate over time (e.g., Gatto, Dambrun, Kerbrat, & De Oliveira, 2010). Experiments that employ situational manipulations of norms relating to humananimal relations (Smith & Louis, 2008) could also be employed in future research.…”
Section: Methodological Implications and Future Research Directionsmentioning
confidence: 99%
“…Indeed, in longitudinal studies, meaningful value changes were found when the time gap was at least 9 months (Hofmann-Towfigh, 2007;Lönnqvist et al, 2011), and the structure of intraindividual value change was less clear when studied over a period of 3 months compared with periods of at least 9 months , Our analytical strategy for testing evidence in line with valuebased self-selection was to examine the values of the target sample at the beginning of the life transition and compare them with a relevant sample. This approach has been effectively used in previous research on self-selection veresus socialization using personality traits and attitudes (e.g,, Gatto et al, 2010;Jackson et al, 2012). A compadson with a relevant sample is particularly important for identifying value-based self-selection because there are strong commonalities in value hierarchies (Schwartz & Bardi, 2001).…”
Section: The Cnrrent Research and Its Analytical Strategymentioning
confidence: 99%
“…A related possibility is that increases in SDO and RWA may also be partially driven by group-based socialization, such as membership in fundamentalist groups in the case of RWA or high-status groups in the case of SDO (Guimond, Dambrun, Michinov, & Duarte, 2003;Poteat, Espelage, & Green, 2007; see also Gatto, Dambrun, Kerbrat & De Oliveira, 2010). Poteat et al (2007), for instance, showed that adolescents' levels of SDO tended to become aligned over time with the average or overall level of SDO expressed by members of their peer group.…”
Section: Overview Of Non-predicted Longitudinal Effectsmentioning
confidence: 99%